Saberes astronômicos na escola normal do Pará: a disciplina cosmografia (1900 -1924) - SOUZA, Elenton Oliveira de (2020)
The present paper seeks the knowledge and To know of astronomy in the discipline Cosmografia in the Normal School of Pará. We will do a research through the bibliographical survey, of Barros (2010), Sobreira (2002) and others, analysis of documents of the Normal School curriculum From Pará in the period from 1900 to 1924, in order to verify the astronomical knowledge taught in the discipline Cosmografia, the regent teacher and the textbook adopted. The text will tell a brief history of the Normal School of Pará, a discipline Cosmography, the concept of Cosmography in the temporal context and its knowledge of astronomy it presents us.